2016
DOI: 10.1002/cmdc.201600477
|View full text |Cite
|
Sign up to set email alerts
|

A Quinacrine Analogue Selective Against Gastric Cancer Cells: Insight from Biochemical and Biophysical Studies

Abstract: One of the earliest synthetic antimalarial drugs, quinacrine, was recently reported as interesting for the treatment of acute myeloid leukemia. Inspired by this and similar findings, we evaluated a set of quinacrine analogues against gastric (MKN-28), colon (Caco-2), and breast (MFC-7) cancer cell lines and one normal human fibroblast cell line (HFF-1). All the compounds, previously developed by us as dual-stage antimalarial leads, displayed antiproliferative activity, and one of the set stood out as selective… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
9
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 95 publications
1
9
0
Order By: Relevance
“…As such, the development of ILs derived from APIs (API-ILs) is an appealing strategy towards the rescuing of drugs that are falling into disuse due to these and other detrimental traits. With this idea in mind, and following our previous promising findings on cinnamic acid conjugates of classical antimalarial drugs [7][8][9][10], we applied the API-IL concept onto such drugs, by disclosing room temperature ionic liquids (RTILs) derived from primaquine (PQ) and cinnamic acids as triple-stage antimalarial hits [11]. The most remarkable property of these RTILs was their increased activity against blood-stage malaria parasites, on which PQ has a practically negligible action [12].…”
Section: Introductionmentioning
confidence: 99%
“…As such, the development of ILs derived from APIs (API-ILs) is an appealing strategy towards the rescuing of drugs that are falling into disuse due to these and other detrimental traits. With this idea in mind, and following our previous promising findings on cinnamic acid conjugates of classical antimalarial drugs [7][8][9][10], we applied the API-IL concept onto such drugs, by disclosing room temperature ionic liquids (RTILs) derived from primaquine (PQ) and cinnamic acids as triple-stage antimalarial hits [11]. The most remarkable property of these RTILs was their increased activity against blood-stage malaria parasites, on which PQ has a practically negligible action [12].…”
Section: Introductionmentioning
confidence: 99%
“…Such observations prompted us, and others, to design and prepare novel derivatives of known antimalarial drugs and evaluate their cytostatic potential . Our efforts have been focused on primaquine (PQ), which is an old drug with many flaws (e.g., induction of hemolytic anemia in individuals lacking glucose‐6‐phosphate dehydrogenase, quick metabolism, degradation to inactive carboxyprimaquine, altering the treatment outcome in dependence of CYP 2D6 enzyme activity) but is currently the only available Plasmodium hypnozoitocide .…”
Section: Introductionmentioning
confidence: 99%
“…Such observations prompted us, and others, to design and preparen ovel derivatives of known antimalarial drugs and evaluatet heir cytostaticp otential. [24][25][26][27][28][29][30][31][32][33][34] Our efforts have been focusedo np rimaquine (PQ), which is an old drug with many flaws (e.g.,induction of hemolytic anemia in individuals lacking glucose-6-phosphate dehydrogenase, quick metabolism, degradationt oi nactive carboxyprimaquine, altering the treatment outcomei nd ependence of CYP2 D6 enzymea ctivity) [35] but is currently the only available Plasmodium hypnozoitocide. [36] We previously showed that variousP Qd erivatives of amides, ureas, bis-ureas, semicarbazides, and acylsemicarbazide-type derivatives possessed significant cytostatic activity against a panel of cancerc ell lines or high selectivity towards the breast adenocarcinoma cell line (MCF-7).…”
Section: Introductionmentioning
confidence: 99%
“…Later on, Gomes et al assessed the action of mepacrine-CA conjugates 12 ( Figure 5) and of analogues where the CA building block was replaced by other acyl moieties, and found that compounds 12 were significantly more selective than the parent drug, mepacrine, against the MFC-7 (4.5 < GI 50 < 24 µM versus 6.0 µM for mepacrine), Caco-2 (3.8 < GI 50 < 35 µM versus 2.4 µM for mepacrine) and, especially, MKN-28 (3.8 < GI 50 < 16 µM versus 2.5 µM for mepacrine) cancer cell lines, as compared to normal HFF-1 cells (GI 50 > 47 µM versus 11 µM for mepacrine). One of the compounds (12, where R 1 = OMe, R 2 = Cl, R = p-F; see Figure 5) stood out for its selective action against the gastric cancer (MKN-28) cells, where the compound is significantly internalized and targets the nucleus, most likely binding to DNA [73].…”
Section: Repurposing Antimalarials For Cancer Via Conjugation To Cinnmentioning
confidence: 99%